Overcoming Security Challenges is Paramount to Ensuring the Success of CPEC - Muhammad Ibrar (Journal of Peace, Development and Communication, 2023)
This study assesses the security threats posed by the China-Pakistan Economic Corridor (CPEC), a major project that employs the Silk Road's One Belt, One Road (OBOR) extension to connect the Kashgar and Gawadar port regions. The CPEC project, which is expected to draw more than $60 billion in investment and be finished in 2030, is viewed as critical to China-Pakistan political and economic ties. The report underlines the CPEC project's ability to address a variety of border-area stability challenges and prevent outside actors from exploiting internal and external ethnic conflicts. As a result, the project is viewed as a critical tool for developing cooperation, alleviating tensions, and building confidence between the two countries. To ensure the success of the CPEC project, the document notes the considerable security issues that must be resolved. These difficulties include geopolitical rivalries, the threat of terrorism, and extremism. The author emphasizes the crucial part that both governments must play in resolving these issues so that the CPEC project can realize its full revolutionary potential. Working together is the only way for the project to truly shift the game and have a big impact on the region's geopolitical and economic landscape.